Conservation of natural resources - Discovery Channel School; Discovery Communications Inc. ([Bethesda, Md.] : Discovery Communications Inc., 2001)
Explain about conservation includes the meaning, process by which plastics bottles are recycled, ecological water treatment system, genetic engineering, etc
Teacher's guide in PDF and Microsoft Word format
System requirements : Windows 95/98, pentium processor 100 MHz and above, 16 MB installed RAM, minimum 25 MB free hard disc space, minimum resolution of 640 X 480, 16-bit color, 4 X CD-ROM drive
System requirements : Power PC macintoch at 100 MHz or better, running system 7.6.1 or higher, minimum of 8 MB available RAM, minimum of 25 MB free had disc space, 640 X 480 resolutions, 16-bit color, 4 X multimedia-compliant CD-ROM drive
Keywords: Conservation of natural resources -- Juvenile literature; Natural resources -- Study and teaching -- Computer programs; Ecology -- Study and teaching -- Computer programs